Archeologia poza archaīos. Przykład obozu jeńców wojennych i internowanych w Tucholi (woj. kujawsko- -pomorskie) - Kobiałka, Dawid; Kostyrko, Mikołaj; Kajda, Kornelia (Folia Praehistorica Posnaniensia, 2016)
This paper is a case study of a prisoner of war and internment camp in Tuchola (Kujawsko-Pomorskie Province, Poland). The camp operated between 1914 and 1923. During the First World War it was run by Germans and later, during the Polish-Soviet War, by the Poles. The site provides a context for discussing two issues around archaeological research of the recent past. The first issue is how archaeology can be used to analyse the transformations of landscapes related to modern armed conflicts. The second point deals with the documentation and analysis of the remains of the camp using ALS derivatives. The main conclusion of this paper is that LiDAR technology can be also a useful tool in the context of approaching landscapes from the recent past.